Find : ∫(2x^2+3)/(x^2 (x^2+9) ) dx;x≠0
This question is similar to Ex 7.5, 18 Chapter 7 Class 12
Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class
CBSE Class 12 Sample Paper for 2024 Boards
Question 2
Question 3 Important
Question 4 Important
Question 5 Important
Question 6 Important
Question 7
Question 8
Question 9
Question 10
Question 11
Question 12
Question 13 Important
Question 14 Important
Question 15 Important
Question 16
Question 17 Important
Question 18
Question 19 [Assertion Reasoning] Important
Question 20 [Assertion Reasoning]
Question 21 (Choice 1) Important
Question 21 (Choice 2)
Question 22 Important
Question 23 (Choice 1)
Question 23 (Choice 2) Important
Question 24
Question 25
Question 26 Important You are here
Question 27
Question 28 (Choice 1)
Question 28 (Choice 2) Important
Question 29 (Choice 1)
Question 29 (Choice 2)
Question 30 (Choice 1) Important
Question 30 (Choice 2)
Question 31
Question 32 Important
Question 33 (Choice 1)
Question 33 (Choice 2) Important
Question 34 Important
Question 35 (Choice 1) Important
Question 35 (Choice 2) Important
Question 36 (i) [Case Based]
Question 36 (ii)
Question 36 (iii) (Choice 1)
Question 36 (iii) (Choice 2)
Question 37 (i) [Case Based]
Question 37 (ii)
Question 37 (iii) (Choice 1) Important
Question 37 (iii) (Choice 2)
Question 38 (i) [Case Based]
Question 38 (ii)
CBSE Class 12 Sample Paper for 2024 Boards
Last updated at Aug. 10, 2023 by Teachoo
This question is similar to Ex 7.5, 18 Chapter 7 Class 12
Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class
(2𝑥^2 + 3)/(𝑥^2 (𝑥^2 + 9) ) Let t = 𝒙^𝟐 = (2𝑡 + 3)/𝑡(𝑡 + 9) We can write (2𝑡 + 3)/𝑡(𝑡 + 9) = 𝑨/𝒕 + 𝑩/((𝒕 + 𝟗) ) (2𝑡 + 3)/𝑡(𝑡 + 9) = (𝐴(𝑡 + 9) +𝐵𝑡)/(𝑡(𝑡 + 9) ) Cancelling denominator 𝟐𝒕+𝟑 = 𝑨(𝒕+𝟗)+𝑩𝒕 Putting t = −𝟗 in (1) 2(−9)+3 = 𝐴(−9+9)+𝐵(−9) −18+3 = 𝐴×0+𝐵(−9) −15 = 0+𝐵(−9) −15 = −9𝐵 B = 15/9 𝑩 = 𝟓/𝟑 Putting t = 𝟎 in (1) 2(0)+3 = 𝐴(0+9)+𝐵(0) 3 = 9𝐴+0 A = 9/3 A = 𝟏/𝟑 Hence we can write (2𝑡 + 3)/𝑡(𝑡 + 9) = (1/3)/𝑡 + (5/3)/((𝑡 + 9 ) ) (2𝑡 + 3)/𝑡(𝑡 + 9) = 1/3𝑡 + 5/(3(𝑡 + 9)) Putting back t = 𝒙^𝟐 (𝟐𝒙^𝟐+ 𝟑)/(𝒙^𝟐 (𝒙^𝟐 + 𝟗) ) = 𝟏/(𝟑𝒙^𝟐 ) + 𝟓/(𝟑(𝒙^(𝟐 )+ 𝟗)) Therefore, ∫1▒(2𝑥^2 + 3)/(𝑥^2 (𝑥^2 +9)) 𝑑𝑥 = ∫1▒〖1/(3𝑥^2 ) 𝑑𝑥"+ " ∫1▒5/(3(𝑥^2+ 9))〗 𝑑𝑥 = 1/3 ∫1▒〖1/𝑥^2 𝑑𝑥" + " 5/3 ∫1▒1/((𝑥^2+ 9))〗 𝑑𝑥 = 𝟏/𝟑 ∫1▒〖𝟏/𝒙^𝟐 𝒅𝒙" + " 𝟓/𝟑 ∫1▒𝟏/((𝒙^𝟐+ 〖(𝟑)〗^𝟐))〗 𝒅𝒙 = 1/3 × (−𝟏)/𝒙 + 5/3 × 𝟏/𝟑 〖𝒕𝒂𝒏〗^(−𝟏)〖 𝒙/𝟑〗 + C = (−𝟏)/𝟑𝒙 + 𝟓/𝟗 〖𝒕𝒂𝒏〗^(−𝟏) (𝒙/𝟑) + C